Improving the Quality of Islamic Elementary School through the Moral Leadership of the Principal - Hartono Hartono; Tamsik Udin; Onwardono Rit Riyanto (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThis study aims to describe the moral leadership of the headmaster in improving the quality of the Madrasah Ibtidaiyah. Using a phenomenological case study,the data were gathered through interviews, observation, and documentation and then analyzed using three stages, namely data reduction, data display, and data verification. The results reveal that the headmaster is capable of bringing the madrasah to become one of the best madrasahs in Banyumas regency, Indonesia. Every leader has his own passion and leadership strategy. The passion of the headmaster is characterized by a self-energy, a belief based on divine values, and a willingness to learn from other schools. There are three strategies of the headmaster in managing the madrasah: 1) the values to be implemented in the madrasah that presents belief in his leadership passion; 2) communication that is done to build up relationships and motivation towards the vision; and 3) collaboration as a representation of the bonding power in building the strength of the madrasah with the power of the community, in this case the studentsâ€™ guardians. Moral leadership integrated with religious and social attitudes greatly helps the leadership role of the principal.Keywords: moral leadership, strategy, quality of Islamic elementary school.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan kepemimpinan moral kepala sekolah dalam meningkatkan mutu madrasah ibtidaiyah. Dengan menggunakan studi kasus dengan pendekatan fenomenologis, data diambil melalui wawancara, observasi dan dokumentasi kemudian dianalisis menggunakan tiga tahap yaitu reduksi data, display data dan verifikasi data. Hasil penelitian mengungkapkan bahwa kepala sekolah mampu membawa madrasah yang dipimpinnya menjadi salah satu madrasah terbaik di Kabupaten Banyumas, Indonesia. Setiap pemimpin memiliki semangat dan strategi kepemimpinannya sendiri. Gairah Kepala Sekolah ditandai dengan energi diri, keyakinan yang dilandasi nilai-nilai ketuhanan, dan kemauan untuk belajar dari sekolah lain sebagai kekuatan pengikat. Tiga strategi kepala madrasah dalam mengelola madrasah adalah: 1) nilai-nilai yang diterapkan di madrasah yang menghadirkan keyakinan akan semangat kepemimpinannya; 2) komunikasi yang dilakukan untuk membangun hubungan dan motivasi menuju visi; dan 3) kolaborasi sebagai representasi kekuatan ikatan dalam membangun kekuatan madrasah dengan kekuatan masyarakat, dalam hal ini wali murid. Kepemimpinan moral yang terintegrasi dengan sikap keagamaan dan sosial sangat membantu peran kepemimpinan kepala sekolah.Kata kunci: kepemimpinan moral, strategi, kualitas madrasah ibtidaiyah.